The THE RELATIONSHIP BETWEEN STUDENTS’ HABIT IN WATCHING ENGLISH TIKTOK AND THEIR VOCABULARY MASTERY IN SENIOR HIGH SCHOOL - Pratama K, Arya Putra; Roslaini (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Students are progressively acquiring new vocabulary from their everyday experiences, particularly through various internet applications, with a particular emphasis on social media. TikTok is a highly global social media application used by many students. Teachers may contemplate utilizing TikTok as an instructional instrument for their students. Therefore, this research aimed to find out whether TikTok influences students’ English vocabulary. To get the data, this research uses an observational quantitative with a cross-sectional design. The instruments used are questionnaire and vocabulary test. Both instruments are given to 125 students of SMA Budi Mulia Tangerang, and SPSS is used for analyzing the data. The result of this research indicates that the students’ habit at SMA Budi Mulia Tangerang comes into good category, and the students’ vocabulary mastery can be categorised into very good category. Then, after analyzing the data, it shows that there is a significant correlation between students’ habit of watching English TikTok and their vocabulary mastery within p-value = 0.009. In this case, it can be said that watching English TikTok gives contribution to students’ vocabulary mastery.